Effects of achievement contexts on the meaning structure of emotion words. Issue 2 (17th February 2018) - Gentsch, Kornelia; Loderer, Kristina; Soriano, Cristina; Fontaine, Johnny R. J.; Eid, Michael; Pekrun, Reinhard; Scherer, Klaus R.
ABSTRACT: Little is known about the impact of context on the meaning of emotion words. In the present study, we used a semantic profiling instrument (GRID) to investigate features representing five emotion components (appraisal, bodily reaction, expression, action tendencies, and feeling) of 11 emotion words in situational contexts involving success or failure. We compared these to the data from an earlier study in which participants evaluated the typicality of features out of context. Profile analyses identified features for which typicality changed as a function of context for all emotion words, except contentment, with appraisal features being most frequently affected. Those context effects occurred for both hypothesised basic and non-basic emotion words. Moreover, both data sets revealed a four-dimensional structure. The four dimensions were largely similar (valence, power, arousal, and novelty). The results suggest that context may not change the underlying dimensionality but affects facets of the meaning of emotion words.